Understanding Turnover Intention in Student Workers: The Role of Compensation and Burnout - Asmadhini Handayani Rahmah; Sofia Ulfa Eka Hadiyanti; Nur Faizah (www.amertainstitute.com, 2025)
This study explores the influence of compensation and burnout on turnover intention among part-time university students. As academic and job demands increase, student workers often face emotional strain and exhaustion, which may lead to a desire to leave their jobs. Data were collected through a survey of part-time student workers in East Kalimantan, Indonesia. The results indicate that fair and satisfactory compensation can reduce turnover intention, while high levels of burnout tend to increase it. These findings highlight the importance of recognizing both psychological well-being and fair rewards in supporting student worker retention. The study offers practical insights for educational institutions and employers to create more supportive and flexible work environments for students balancing study and work.